Double-duty actions addressing the double burden of malnutrition among adolescents aged 10–19: protocol for a scoping review - Zhao, Shuangyu; Shinde, Sachin; Mastan, Melinda; Fawzi, Wafaie; Tang, Kun (Frontiers in Public Health, 2024)
Background The global adolescent population faces the challenge of the double burden of malnutrition (DBM), characterized by the coexistence of undernutrition and overweight/obesity, including diet-related non-communicable diseases (NCDs). This dual challenge, prevalent across various socio-economic backgrounds, necessitates double-duty actions, i.e. integrated interventions designed to concurrently address both sets of conditions. These actions are critical for fostering the overall health and well-being of adolescents. The objective of this review is to describe the content, setting, and delivery mechanisms of double-duty actions, synthesize their impacts on adolescents' nutritional status, and offer policy and program implications for future interventions. Methods As part of this scoping review, we will conduct a comprehensive search across multiple databases, including MEDLINE, Embase, CENTRAL, CINAHL, and Google Scholar, to identify relevant interventions, programs, policies, guidelines, evaluation studies, and strategies targeting DBM among adolescents aged 10–19 years. Inclusion criteria encompass a range of evidence sources with methodologically sound and well-described study designs. All full-text articles and abstracts will be independently screened by two reviewers to ensure a comprehensive inclusion of papers that align with the established criteria. The final protocol is available on Open Science Forum (https://osf.io/kxapb). Discussion Addressing DBM through integrated double-duty actions is crucial for achieving global nutrition and public health goals. However, challenges persist in the form of uncoordinated efforts, lack of comprehensive evidence for what interventions work among adolescents, and the need for context-specific strategies to effectively address the heterogeneity of DBM. The results of this scoping review may provide evidence for future policies and interventions, emphasizing integrated, multi-sectoral strategies tailored to the unique needs of the adolescent population.